Assessment of bullet effectiveness based on a human vulnerability model. Issue 3 (25th December 2017) - Liu, Susu; Xu, C; Wen, Y; Li, G; Zhou, J
Abstract : Introduction: Penetrating wounds from explosively propelled fragments and bullets are the most common causes of combat injury. There is a requirement to assess the potential effectiveness of bullets penetrating human tissues in order to optimise preventive measures and wound trauma management. Methods: An advanced voxel model based on the Chinese Visible Human data was built. A digital human vulnerability model was established in combination with wound reconstruction and vulnerability assessment rules, in which wound penetration profiles were obtained by recreating the penetration of projectiles into ballistic gelatin. An effectiveness evaluation method of bullet penetration using the Abbreviated Injury Scale (AIS) was developed and solved using the Monte Carlo sampling method. Results: The effectiveness of rifle bullets was demonstrated to increase with increasing velocity in the range of 300–700 m/s. When imparting the same energy, the effectiveness of the 5.56 mm bullet was higher than the 7.62 mm bullet in this model. Conclusions: The superimposition of simulant penetration profiles produced from ballistic gelatin simulant has been used to predict wound tracts in damaged tissues. The authors recognise that determining clinical effectiveness based on the AIS scores alone without verification of outcome by review of clinical hospital records means that this technique should be seen more as a manner of comparing the effectiveness of bullets than an injury prediction model.